Developing effective narrative exposure therapy interventions for Saudi firefighters - Alghamdi, Mohammed (2015)
Firefighters have a high likelihood of being exposed to a variety of traumatic events. The psychological cost of this exposure may be an increased risk of long-term problems such as PTSD symptoms, depression and anxiety. Saudi firefighters in Makkah province are often exposed to elevated levels of potentially traumatising events through the course of their work which can affect them physically and psychologically. However, providing sufficient mental health professionals is difficult due to the absence of psychological trauma care in Saudi Arabia and Saudi culture associated with the psychological support. The aim of this thesis is to understanding the psychological impact of being a firefighter and seeing whether narrative exposure therapy (NET) is an effective treatment for traumatised Saudi firefighters. Three studies were conducted In order to achieve these aims. The first administered questionnaires to 200 Saudi firefighters; the second was a qualitative study comprising of semi-structure life story interviews with 9 traumatised Saudi firefighters, whilst the final randomized control trial (RCT) examined the effectiveness of NET with 34 Saudi firefighters with PTSD. A high prevalence rate of PTSD (57%), anxiety (44.4%), and depression (53.3%) symptoms with limited mental health support were reported. Single firefighters reported PTSD symptoms and the use of passive coping strategies more than the married firefighters. The results also revealed that marriage was associated with low levels of PTSD, while high levels of PTSD correlated with anxiety, depression, and with passive coping strategies. The qualitative study illustrated themes and subthemes reflected family life, education, experience of being firefighters, traumatic, coping strategies. Two narrative analysis cases presented with the life plot trend with the positive impact of the individual’s life story interview which inform the using of narrative technique in the intervention study. The RCT study demonstrated a significant reduction in PTSD, anxiety, and depression symptoms after 6 weeks, but this was not sustained at 3 and 6 months.